EVALUATION OF THE CARBON FOOTPRINT OF THE COFFEE PRODUCTION CHAIN: CASE STUDY OF THE FINCA TRIUNFO VERDE, CHIAPAS, MÉXICO - Adán Villa-Herrera; Martin Alejandro Bolaños-Gonzalez; Fernando Paz-Pellat; Jose Manuel Salvador-Castillo; Luz María Ramirez-Armas; Carolina Villagomez-Jimenez (Tropical and Subtropical Agroecosystems)
Background. The carbon footprint (CF) quantifies the total greenhouse gas (GHG) emissions generated by human activities. Reducing the CF of agricultural products is essential for mitigating global warming. Objective. To quantify the CF in organic shade-grown coffee production in two modalities: green coffee for export and ground, packaged coffee for the local market at Finca Triunfo Verde S.C., Chiapas, Mexico. Methodology. During the 2023–2024 production cycle, 458 plots across 32 communities in eight municipalities of the Sierra Madre de Chiapas were evaluated. GHG emissions were estimated according to IPCC guidelines and the PAS-2050 standard. Results. The average total CF was 0.909 kg CO₂e kg⁻¹ for export green coffee and 1.014 kg CO₂e kg⁻¹ for locally marketed coffee. The wet processing phase had the highest impact in both cases, primarily due to methane emissions from pulp decomposition (0.289 kg CO2e kg⁻¹) and nitrous oxide emissions from wastewater (0.266 kg CO2e kg⁻¹). Transportation contributed 0.238 kg CO2e kg⁻¹ for export coffee and 0.211 kg CO2e kg⁻¹ for local market coffee due to fuel consumption. Together, these activities accounted for 87.18% and 75.54% of the total CF for export and local market coffee, respectively. Implications. Optimizing coffee by-product management, adopting clean energy, and improving transportation efficiency could significantly reduce CF. Conclusion. Wet processing was the most significant impactful phase in both production modalities. Pulp decomposition contributed 31.77% to the CF of export coffee and 28.48% to local market coffee. Wastewater emissions represented 29.28% and 26.25%, respectively, while transportation represented 26.13% and 20.81% of the CF for export and local market coffee.